2001
DOI: 10.1183/09031936.01.00014101
|View full text |Cite
|
Sign up to set email alerts
|

The voluntary drive to breathe is not decreased in hypercapnic patients with severe COPD

Abstract: The voluntary drive to breathe is not decreased in hypercapnic patients with severe COPD. A. Topeli, F. Laghi, M.J. Tobin. #ERS Journals Ltd 2001. ABSTRACT: How do the respiratory centres of patients with chronic obstructive pulmonary disease (COPD) and hypercapnia respond to acute increases in inspiratory load? A depressed respiratory motor output has long been postulated, but studies on this issue have yielded inconsistent results, partly due to limitations of investigative techniques. Many of these limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
4
20
0
Order By: Relevance
“…Contrary to our hypotheses, our results show that patients with COPD have comparable diaphragm thickness and contraction to that of normal subjects. Th is is consistent with the work of Topeli et al, 16 who reported normal diaphragm structure, diaphragm function, and respiratory drive in patients with COPD.…”
Section: Discussionsupporting
confidence: 82%
“…Contrary to our hypotheses, our results show that patients with COPD have comparable diaphragm thickness and contraction to that of normal subjects. Th is is consistent with the work of Topeli et al, 16 who reported normal diaphragm structure, diaphragm function, and respiratory drive in patients with COPD.…”
Section: Discussionsupporting
confidence: 82%
“…The mean fibre area was not different, which suggests that hypertrophy did not compensate significantly. Further, the diaphragm may already be maximally activated during acute exacerbations in some individuals with COPD [8]. In this case, the areas of disrupted sarcoplasm and collagen accumulation observed in this study may have contributed to a peri mortem loss of inspiratory force.…”
Section: Discussionmentioning
confidence: 86%
“…It is likely that during repeated or prolonged exacerbations, the COPD diaphragm may experience maximal activation leading to injury and incomplete regeneration, as shown in animal models [8][9][10][11]. Although individuals with COPD show a high susceptibility to exertioninduced diaphragm injury following inspiratory resistive loading [12], the extent of injury has, to date, been examined only in stable COPD patients.…”
mentioning
confidence: 99%
“…Second, as compared to FA-exposed mice, the greatest change of ventilation in CS-exposed mice was the rapid breathing, leading to an increase of V̇E. Actually, a rapid breathing rate has often been observed in hypercapnic COPD patients (Altose et al 1977;Fahey et al 1983;Gorini et al 1990;van de Ven et al 2002), although the baseline ventilation has been reported to be increased (Gorini et al 1990;Topeli et al 2001), decreased (Altose et al 1977), or unchanged (Sorli et al 1978;Montes de Oca et al 1998;van de Ven et al 2002). Additionally, we also found a slightly, but significantly higher HR in CSexposed mice as compared to FA-exposed mice (Fig.…”
Section: It Is Novel That the Major Symptoms Of Anesthetized C3h/hen mentioning
confidence: 99%